Pengaruh Komunikasi Horizontal dan Budaya Organisasi terhadap Kinerja Karyawan Organisasi Jasa Keuangan di Batam - Adi Irawan Setiyanto; Yiyik Dwi Pangesti Septiyani (Politeknik Negeri Batam, 2016)
The achievement of organizational goals is influenced by organizational behavior is a reflection of behaviors and attitudes of those within the scope of the organization. Communication and organizational culture has an important role in the company. This study aims to determine the effect of horizontal communication and organizational culture on employee performance. Respondents in this study were 205 permanent employees and contract work in the financial services organization Batam, a data analysis technique used is multiple regression analysis. The results of this study indicate that horizontal and organization culture significant effect on employee performance.